UMP Publisher's new office - Muhammad Azli, Shukri (Penerbit UMP, 2012)
UMP Publisher plays a role as a centre responsible in publishing various academic materials, in line with UMP's publication's policy. Since the set up of the Publishing Unit (PU), which was previously placed under Research Management Centre (RMC) and its inception on July 1, 2007, UMP Publication has grown rapidly and become proactive.